Energy consumption analysis for WLAN discovery schemes in converged networks - JIANG Jun-feng; CAO Zhi-gang (Tongxin xuebao)
The terminal energy consumption of WLAN discovery schemes was considered for wireless heterogeneous networks, which were the integration of 3GPP （third generation partnership project） cellular networks and WLAN （wire- less local area network）. Utilizing the terminal energy consumption model proposed, the energy consumption of paging based WLAN discovery scheme and the other four WLAN discovery schemes was analyzed. Analysis results indicate that paging based scheme consumes least energy of all the schemes. The scheme that keeps the terminal periodically scanning in the cells with WLAN consumes the second least energy. It is also shown that the scheme that keeps the terminal periodic scanning in the cell with WLAN and that keeps the terminal periodic scanning in all zones consume comparable energy.